2019
DOI: 10.1111/jdi.13185
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical activity and sedentary time on glycated hemoglobin levels and body composition: Cross‐sectional study using outpatient clinical data of Japanese patients with type 2 diabetes

Abstract: Aims/Introduction: This study examined the association among sedentary time (ST), physical activity (PA), glycated hemoglobin and body composition in Japanese type 2 diabetes patients. Materials and Methods: Patients with type 2 diabetes who visited the outpatient clinic at Kawasaki Medical School Hospital, Okayama, Japan, comprised the study's participants. Self-administered International Physical Activity Questionnaire short forms were obtained and analyzed for 1,053 patients, including 158 patients for whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…There are some reports on this device in medical facilities for patients with metabolic syndrome and diabetes, medical examinations, and health guidance after medical examinations. [20][21][22] In sleep medical facilities, which see many obese OSA patients with VF accumulation, there have not been any reports about the use of this device for direct measurement of VFA by the A-BIA method. We were able to use it in our private sleep clinic without undue burden on patients and staff.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports on this device in medical facilities for patients with metabolic syndrome and diabetes, medical examinations, and health guidance after medical examinations. [20][21][22] In sleep medical facilities, which see many obese OSA patients with VF accumulation, there have not been any reports about the use of this device for direct measurement of VFA by the A-BIA method. We were able to use it in our private sleep clinic without undue burden on patients and staff.…”
Section: Discussionmentioning
confidence: 99%
“…Japan is one of the countries with the longest ST; the average ST in Japanese adults was 7.0 h/day [ 37 ], investigated with the help of IPAQ in a cross-sectional study. A recent Japanese cross-sectional study that used IPAQ on 1053 patients with T2D showed that average ST was 6.0 h/day [ 38 ]. However, in T1D patients, little is known about average or median ST.…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan 11 kepustakaan yang dikaji, sepuluh diantaranya menjelaskan pengaruh aktivitas fisik terhadap massa lemak visceral [13][14][15]17,[21][22][23] . Pada penelitian ini didapatkan bahwa, tingkat aktivitas fisik rendah umumnya diikuti dengan tingginya massa lemak visceral dan lingkar pinggang 14,15,17,[21][22][23] .…”
Section: Gambar 1 Diagram Alur Yang Menggambarkan Berbagai Tahapan Pa...unclassified